STRATEGI PENCEGAHAN DAN PEMBERANTASAN PENCUCIAN UANG DAN TAHAPAN-TAHAPAN TINDAK PIDANA PENCUCIAN UANG - Kurniati; Mardiyati, Siti (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Money laundering prevention and suppression strategies rely on presumption of guilt, which means that the person who owns property allegedly derived from a crime must prove that the property does not come from a criminal offence. Theoretically, the principle of probability balance is used to support the reverse proof of the origin of property property.The money-laundering process consists of several steps, such as placement, coating or coating, and integration or merger.